The proline 7 substitution in the preproneuropeptide Y is associated with higher hepatic lipase activity in vivo - Schiekofer, Stephan; Kleber, Marcus E.; März, Winfried (International journal of endocrinology, 2017)
Hepatic lipase (HL) functions as a lipolytic enzyme that hydrolyzes triglycerides and phospholipids present in circulating plasma lipoproteins. Plasma HL activity is known to be regulated by hormonal and metabolic factors, but HL responsiveness to insulin as well as its role in modulating atherosclerotic risk is still controversial. We investigated on the influence of a known polymorphism in the neurotransmitter neuropeptide Y (NPY) on HL activity in two different cohorts consisting of diabetic and nondiabetic patients. HL activity was 24% and 34% higher on nondiabetic and diabetic subjects in the presence of the 7Pro allele in NPY, respectively. The presence of the 7Pro allele was an independent predictor of HL activity in multivariate analyses in both cohorts. These data suggest a regulatory effect of NPY on HL activity. Among carriers of the 7Pro allele, we also found a statistically significant lower absolute number of infarctions compared to noncarriers () and a nonsignificant trend towards less myocardial infarction in the 7Pro allele diabetic carriers (). In conclusion, the common 7Pro allele in NPY was associated with higher HL activity in nondiabetic and diabetic subjects and its presence seems to coincide with a lower frequency of certain cardiovascular events.